Analisis Komunitas Online Storial - Jemmima Averina Handrijatmoko; Made Galuh Inggita Amaranila Santa; Novera Agellina Sunaidi; Jessica Gresina (Universitas Semarang, 2022)
Digitalization has brought many changes to human life. One of the actual examples is the emergence of communities in the field of literacy that move online, such as the “Storial” community. Komunitas Storial is a community engaged in literacy, especially writing and reading digital novels on the Storial.co application. In this journal, we will analyze the community using the Participatory Action Research method. The author will focus on analyzing several aspects of the community to find the core problems, as well as finding the right solution to solve the existing problems. The results of the analysis shows that the main problem of the community is the lack of reader members and structural conditions that are still unclear. As a solution, the community can improve the structural conditions of the community and balance the position between members with reading and writing roles.